Chrononutrition behavior during the COVID-19 pandemic and its relationship with body weight among college students - Juliana, Norsham; Teng, Nur Islami Mohd Fahmi; Hairudin, Khairunnisa Fazira; Wan Abdul Fatah, Wan Asma; Das, Srijit (Frontiers in Nutrition, 2023)
Students in colleges are exposed to unhealthy lifestyles and poor dietary choices. They are at risk of being overweight, skipping meals, and developing eating disorders. However, there is a paucity of information on their chrononutrition behavior, which is very important, especially concerning the timing of food consumption across the day. Therefore, the present study aimed to investigate chrononutrition behavior and its potential association with body weight status among college students in Malaysia. This cross-sectional study was conducted on 409 college students aged above 18 in Malaysia. The chrononutrition behavior was assessed using the validated Chrononutrition Profile Questionnaire (CP-Q). The questionnaire was distributed using an online platform. Participants self-reported their body weight and height, and the Body Mass Index (BMI) was computed. Data were analyzed using the SPSS software. A total of 409 participants were recruited, with a mean age of 21.5 ± 2.2 years. The prevalence of underweight, normal, and overweight was 24.7%, 49.4%, and 25.9%, respectively. The chrononutrition behavior revealed that participants ate breakfast about four times/week (mean 4.27 ± 2.43 days), and only 135 (33.0%) consumed breakfast daily. The largest meal consumed was during lunch (75.8%), and the mean of snacking after the last meal was 3.23 ± 2.01 days. The prevalence of night eating was low, and most participants (70.9) did not wake up at night to eat. The frequency, however, was significantly higher in the underweight group compared to the normal weight group (p<0.05). We observed a significant association between BMI and eating window, evening latency, evening eating, and night eating. It was found that the underweight had a poor eating window (p<0.01), poor evening latency (p<0.01), poor evening eating (p<0.01), and poor night eating (p<0.05) compared to those with normal and overweight BMI groups. In contrast to predictions, poor chrononutrition behavior was more likely to predict being underweight compared to normal (p<0.05). Underweight young adults are more likely to have poor chrononutrition behavior. The results of the present study suggest that future nutrition education should also focus on the chrononutrition behavior of college students.